Alternatives to slash & burn: a global strategy: special project for presentation to the global steering group (GSG): first phase January 1993-December 1997 - International Center for Tropical Agriculture (International Center for Research in Agroforestry, 1992)
It is estimated that shifting cultivation accounts for about 70 percent of the deforestation in Africa, 50 percent in Asia, and 30 percent in Latin America of the 14 million hectares of tropical moist forests currently destroyed every year. Tropical deforestation is responsible for 18 percent of current global warming, for most of the decimation of plant and animal genetic diversity, and for threatening the stability of many watersheds. Landless farmers from crowded areas migrate to the forested areas and attempt to make a living by slash and burn, which results in unsustainable agriculture and continuing rainforest destruction. Sustainable alternatives to slash and burn would enable millions of poor farmers to make an adequate living without destroying additional forests. Research conducted at several locations for many years shows hope that for every hectare put into promising alternatives, five to ten hectares of tropical rainforest can be spared from the shifting cultivator`s axe every year. Several international centers have decided to join efforts with national research systems (NARS) to formulate a research and development strategy that provides viable alternatives to slash and burn agriculture on a worldwide basis. The strategy focuses on two main targets: 1) reclamation of already deforested lands such as secondary forest fallows and abandoned grasslands and 2) prevention of damages by deforestation itself. The strategy consists of three main components: 1) developing and testing alternative slash-and-burn technologies for small-scale farms, adapted to specific ecoregions within the humid tropics, 2) linking environmentally-oriented strategies with socioeconomic policies that provide incentives for such technologies and disincentives to further deforestation and 3) designing effective economically sound and socially acceptable rainforest conservation methods.